Development of Mathematics Learning Devices with Problem Based Learning Models Assisted by Geogebra to Enhance Student’s Understanding of Mathematical Concept - Zetriuslita Zetriuslita (International Journal on Teaching and Learning Mathematics, 2025)
This study aims to produce a mathematics learning device with Problem Based Learning (PBL) models assisted by Geogebra to enhance student’s understanding of mathematical concept on a linear program that has been valid, practical, and effective. Method of research used Research and Development (R and D) and the development model design used the ADDIE model with five stages are: 1) Analysis, 2) Design, 3) Development, 4) Implementation and 5) Evaluation. The data collection techniques used were tests, validation, and response questionnaire. The data collection instrument used were the validation sheet, teacher response questionnaire, student response questionnaire, pretest, and posttest. The data analysis technique used is validation, practical, and effective. The average validation Syllabus was 100% and 97,41% of which are very valid criteria. And for the average validation of Learning Implementation Plan (LIP) was 100% and 97,73% which are very valid criteria. The average validation of Students Worksheets (SW) was 100% and 90,02% which are very valid criteria. The average teacher response questionnaire of LIP was 96,42% which is very practiced and the intermediate student's response questionnaire of SW was 86,91% which is very practice. The average of N-Gain score was 80% which is effective. Based on the results it can be concluded that the development of mathematical learning devices with PBL models assisted by Geogebra to enhance student’s understanding mathematical concept has produced mathematics learning devices which valid, practical, and effective. So that the learning device is feasible to use.